The Impact of Family-Centered Care on Resilience and Depression Levels among Cancer Patients at Dr. OEN Solo - Tunjung Sri Yulianti; Diyono Diyono; Sri Aminingsih; Budi Kristanto; Tri Yahya Cristina; Yayuk Dwi Oktiva; Fatimatuzzahra Khairunnisa; Maria Anggraini (STIKES Adi Husada, 2026)
Cancer patients undergoing chemotherapy often experience psychological distress, physical changes, and long-term care needs that may affect their resilience and level of depression. Family involvement is essential in palliative care because families can provide emotional support, psychological assistance, daily care, and help patients make decisions related to treatment and end-of-life preferences. This study aimed to determine the effect of Family-Centered Care on resilience and depression among cancer patients receiving chemotherapy at the Chemotherapy Unit of Dr. OEN Kandang Sapi Hospital, Solo. This study used a quasi-experimental design with a one-group pretest and posttest approach. The participants were cancer patients undergoing chemotherapy who were selected using total sampling. Data were collected using a Family-Centered Care implementation evaluation checklist, a resilience questionnaire, and a depression assessment instrument. Data were analyzed using the Wilcoxon signed-rank test. The results showed a decrease in depression levels and an increase in resilience after the implementation of Family-Centered Care. These findings indicate that Family-Centered Care has a positive effect on reducing depression and improving resilience among cancer patients. Therefore, strengthening family involvement in palliative and oncology nursing care is important to support the psychological well-being of patients undergoing cancer treatment.